'Neighbour smoke'—exposure to secondhand smoke in multiunit dwellings in Denmark in 2010: a cross-sectional study. Issue 3 (12th June 2012) - Køster, Brian; Brink, Anne-Line; Clemmensen, Inge Haunstrup
Abstract : Background: 'Neighbour smoke' is transfer of secondhand smoke between apartments including shared areas, such as hallways, community rooms and stairwells in multiunit dwellings and is an emerging issue for public health and health equity. Objective: To describe the prevalence of exposure to neighbour smoke in Denmark. Methods: A population-based sample of 5049 respondents (2183 in multiunit dwellings) living in Denmark aged ≥15 years completed a questionnaire in 2010 on tobacco-related behaviour and exposure to secondhand smoke. The authors examined the relations between exposure to neighbour smoke, own smoking, smoking inside the home, type of residence and demographic factors with descriptive statistics and logistic regression analysis. Results: In this sample, 22% of those living in multiunit dwellings reported exposure to neighbour smoke. Of respondents living in apartments, 41% preferred to live in a building in which smoking is banned. Smoke-free buildings were preferred by 58% of persons exposed to neighbour smoke compared with 37% of persons not exposed. Of the smokers (daily and occasional), 14% preferred to live in a smoke-free building; 31% never smoked indoors in their own home. Conclusions: The only way to avoid absorbing tobacco smoke from neighbours is to live in a smoke-free multiunit dwelling. There is great demand for such dwellings, especially by young people, people with children and people exposed to neighbour smoke, as well as by people who smoke.